Ta có : x2 - 2xy + y2 + 1 = (x - y)2 + 1
Vì : \(\left(x-y\right)^2\ge0\forall x\in R\)
Nên : \(\left(x-y\right)^2+1\ge1\forall x\in R\)
Suy ra : \(\left(x-y\right)^2+1>0\forall x\in R\)
Vậy x2 - 2xy + y2 + 1 \(>0\forall x\in R\)
Ta có : x - x2 - 1
= -(x2 - x + 1)
\(=-\left(x^2-x+\frac{1}{4}+\frac{3}{4}\right)\)
\(=-\left(x^2-x+\frac{1}{4}\right)-\frac{3}{4}\)
\(=-\left(x-\frac{1}{2}\right)^2-\frac{3}{4}\)
Vì : \(-\left(x-\frac{1}{2}\right)^2\le0\forall x\in R\)
Nên : \(-\left(x-\frac{1}{2}\right)^2-\frac{3}{4}\le-\frac{3}{4}< 0\)
Vậy x - x2 - 1 \(< 0\forall x\in R\)
hỏi tí cái chữ A ngược đó là gì vậy bạn